Valoración de la condición física de los escolares de 13 a 14 años del distrito Riobamba – Chambo, provincia de Chimborazo. - Ilbay Vicuña, Jorge Luis (2017)
The present research project is descriptive non–experimental cross-sectional, the character of the research was mixed, applied to a simple of 200 students, of which 150 belong to the Educational Unit “Riobamba” and to 50 to the Educational Unit “Leonidas Garcia”, representing 3,34% of the total population of students in the district under study, with a mean age of 13,62 years. The main objective of this research is to examine the fitness levels of the sample under study, for the valuation, data collection and obtaining of results we used the Battery Alpha Fitness valued and validated for this type of studies, while for the verification statistical analysis of the obtained results was applied the statistical package SPSS version 22,00 IBM, performing a Kolmogorov-Smirnov normality test for samples > 60 data, for the parametric variables a T-Student test for single samples and for non-parametric variables one Kolmogorv-Smirnov test for a sample. For the analysis of the qualitative variables of the study, a frequency determination and non-parametric Pearson Chi-Square test were applied. Among the main results we have that in the BMI 58,2% of masculine gender and 53,7% of feminine gender are in an average level according to the varemos of the test; Whereas in the maximum force of the upper train the 59,5% of masculine gender and 78,5% of feminine gender are in a very low level; As in the explosive force test 34,2% of men and 38,8% of women are at a very low level; In addition in the test of speed-agility 4x10 m. 32,9% of males are at an average level and 47,9% of females are at a low level; Also in the test of round trip of 20 m. 87,3% male and 86,9% female are at a low level.